Changes from 1986 to 2018 in the prevalence of obesity and overweight, metabolic control and treatment in children with type 1 diabetes mellitus in a Mediterranean area of Southeast Spain - María Teresa Pastor-Fajardo; María Teresa Fajardo-Giménez; Vicente María Bosch-Giménez; José Pastor-Rosado (BMC, 2022)
Abstract Background In recent decades, a global increase in the prevalence of childhood overweight and obesity has been observed in children and adolescents with type 1 diabetes. Methods This retrospective, cross-sectional, population study examined three groups (1986, 2007, and 2018) of children and adolescents aged < 16 years diagnosed with type 1 diabetes. Overweight and obesity were defined according to the World Health Organization recommendations. Results The prevalence of overweight and obesity in diabetic children and adolescents was 30.2% (95% CI: 23.1-38.3). There was a significant increase from 1986 to 2007 (11.9% to 41.7%, p = 0.002) and from 1986 to 2018 (11.9% to 34.8%, p = 0.012), but no significant differences were found from 2007 to 2018 (41.7% to 34.8%, p = 0.492). The age at diagnosis was lower in the group with excess body mass (p = 0.037). No significant differences were observed in age (p = 0.690), duration of diabetes (p = 0.163), distribution according to sex (p = 0.452), metabolic control (HbA1c, p = 0.909), or insulin units kg/day (p = 0.566), between diabetic patients with overweight or obesity and those with normal weight. From 2007 to 2018, the use of insulin analogs (p = 0.009) and a higher number of insulin doses (p = 0.007) increased significantly, with no increase in the prevalence of overweight and obesity. Conclusions The prevalence of overweight and obesity in diabetic children and adolescents increased in the 1990s and the beginning of the twenty-first century, with stabilization in the last decade. Metabolic control and DM1 treatment showed no association with this trend.